Preserving Malaysian Folktales Through Mobile AR Application: Sumpahan Ikan Tapah - Mohd Yusof, Muhammad Afif; Masmuzidin, Masyarah Zulhaida (Journal of Computing Technologies and Creative Content, 2021)
Malay folktales can provide us with variety of benefits, including moral values and cultural values. This involves being a positive role model, honouring traditions, seeing the world in a new way. Folktales also aid in development of healthy behaviour. People on the other hand, prefer to overlook the positive attributes they may learn from folktales and instead want to hand out the smartphones. As a result, upcoming generations will be less familiar with Malay folktales. The exponential development of smartphones, on the other hand, presents a possibility to build a new gate to conserve folktales. The experiences will enrich the user's learning and narrative experience by introducing a different kind of edutainment that combines augmented reality (AR) and a storybook. This study is being conducted in order to incorporate Augmented Reality as a storytelling medium. The ADDIE model was chosen as the primary methodology for developing Augmented Reality Storytelling. The accessibility of Augmented Reality folktales for children under the age of 18 is investigated.  As a result, Malay folktales will be preserved for future generations.